SKILLS AIMED AT DEVELOPING THE PROFESSIONAL COMPETENCE IN THE PROCESS OF TEACHER TRAINING (Web of Discoveries: Journal of Analysis and Inventions, 2023)
This article analyzes professional competence, qualification requirements for modern specialists, effective use of methods and tools aimed at forming their professional competence in the process of training informatics and information technology teachers.